HUBUNGAN ANTARA SKOR WIBOWO DAN SKOR RANDHAWA DENGAN TINGKAT KESULITAN KOLESISTEKTOMI LAPAROSKOPI - Sorayya, Laina; Wibowo, Agung Ary; Yuliana, Ida; Poerwosusanta, Hery; Rosida, Lena (Universitas Lambung Mangkurat, 2024)
Abstract: Wibowo and Randhawa score are preoperative scoring systems to predict the difficulty of laparoscopic cholecystectomy. Allegedly, the duration of surgery lengthens as the score increases. Variable difference of the two scores may also be associated with their effectiveness difference in predicting the difficulty of surgery. This study aimed to determine the correlation and difference between Wibowo and Randhawa score with the difficulty of laparoscopic cholecystectomy. This study is an observational analytical correlation and comparative study with a prospective cohort approach. The correlation between the score and the difficulty of surgery was analyzed by simple linear regression test, while the effectiveness difference was analyzed by binomial logistic regression test. There was a weak positive correlation that’s significant between Randhawa score and the difficulty of surgery (r = 0,406; B = 3,017; p = 0,009) and moderate positive correlation that’s significant between Wibowo score and the difficulty of surgery (r = 0,540; B = 3,618; p = 0,001). There was no significant difference between the two scores in predicting the difficulty of surgery (RR 1,523; p = 0.498). An increasing score would lengthen the duration of surgery. Wibowo score was more effective than Randhawa’s, but not significant. Keywords: laparoscopic cholecystectomy, Wibowo score, Randhawa score, level of difficulty, duration Abstrak: Skor Wibowo dan Randhawa merupakan sistem skoring preoperatif untuk memprediksi tingkat kesulitan kolesistektomi laparoskopi. Peningkatan skor diduga berhubungan dengan pemanjangan durasi operasi. Perbedaan variabel penilaian pada kedua skor diduga juga berhubungan dengan perbedaan efektivitasnya dalam memprediksi tingkat kesulitan operasi. Penelitian bertujuan untuk mengetahui hubungan dan perbedaan antara kedua skor tersebut dengan tingkat kesulitan kolesistektomi laparoskopi. Penelitian bersifat observasional analitik korelasional dan komparatif dengan pendekatan kohort prospektif. Hubungan kedua skor dengan tingkat kesulitan operasi dianalisis dengan uji regresi linier sederhana, sedangkan perbedaan efektivitasnya dianalisis dengan uji regresi logistik binomial. Terdapat korelasi positif tingkat lemah yang bermakna antara skor Randhawa dengan tingkat kesulitan operasi (r = 0,406; B = 3,017; p = 0,009) dan korelasi positif tingkat sedang yang bermakna antara skor Wibowo dengan tingkat kesulitan operasi (r = 0,540; B = 3,618; p = 0,001). Tidak terdapat perbedaan yang bermakna antara kedua skor tersebut dalam memprediksi tingkat kesulitan operasi (RR 1,523; p = 0,498). Peningkatan skor menyebabkan pemanjangan durasi operasi. Skor Wibowo lebih efektif daripada skor Randhawa, tetapi tidak bermakna. Kata-kata kunci: kolesistektomi laparoskopi, skor Wibowo, skor Randhawa, tingkat kesulitan, durasi